PENGGUNAAN ARSIP UNTUK KEGIATAN ADMINISTRASI: TINJAUAN DI KOTA YOGYAKARTA: Array - Lastria Nurtanzila; Anisa Nurpita (Arsip Nasional Republik Indonesia, 2018)
Administration business are all forms of activities done by administrator start from making, legalizing, implementing and evaluating policy. Those activities are records-connected. Records are source of implementing administrative businesses all the way from bottom to top. The research aims to observe the records use of administration businesses at the city of Yogyakarta. This research uses records management and administration businesses principles, and mix method wherein data triangulation are gathered through simple survey, interview and observation. The results are records are needed for implementing administration businesses at the city of Yogyakarta. The needs of skillful resources of archivist, records storing and records maintaining are to be next priorities for records management at the city of Yogyakarta.